2016
DOI: 10.1002/jca.21503
|View full text |Cite
|
Sign up to set email alerts
|

“Black cloud” vs. “white cloud” physicians – Myth or reality in apheresis medicine?

Abstract: The results of this pilot study may support the common perception that some physicians or nurses are either "black cloud" or "white cloud". A larger, multi-center study population is needed to validate the results of this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
4
1
1
Order By: Relevance
“…In conclusion, unlike the results obtained in the pilot study, the findings from this prospective 35‐month confirmation study did not support the common perception that physicians or nurses maybe either “black clouds” or “white clouds.” Additionally, there was no statistically significant association between “black‐cloud” events and the year, day of the week, month, or season.…”
Section: Descriptive Statistics (N = 1066)contrasting
confidence: 99%
See 3 more Smart Citations
“…In conclusion, unlike the results obtained in the pilot study, the findings from this prospective 35‐month confirmation study did not support the common perception that physicians or nurses maybe either “black clouds” or “white clouds.” Additionally, there was no statistically significant association between “black‐cloud” events and the year, day of the week, month, or season.…”
Section: Descriptive Statistics (N = 1066)contrasting
confidence: 99%
“…Other parameters collected include the treating physician, apheresis nurse, type of emergent apheresis procedure, and day of the week, month, and season as determined by the astronomical calendar. The details of this follow‐up study were similar to the pilot study published previously . As the data were count data and that the goal is to test the occurrence of the “black‐cloud” events between different groups, Chi‐square analysis was performed.…”
Section: Descriptive Statistics (N = 1066)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although association rules were initially developed for consumer market–based analysis, these rules are often successfully applied to other research areas, including health care. For example, Ivancevic et al (2015) identified risk factors associated with early childhood caries, Pham, Raju, Jiang, and Williams (2016) assessed the black-cloud versus white-cloud phenomenon in apheresis medicine, and Kost, Littenberg, and Chen (2012) demonstrated disease specific co-occurrences using Association Rules.…”
Section: Discussionmentioning
confidence: 99%